2019
DOI: 10.1121/1.5087126
|View full text |Cite
|
Sign up to set email alerts
|

The effects of classroom noise on the reading comprehension of adolescents

Abstract: An investigation has been carried out to examine the impact of different levels of classroom noise on adolescents' performance on reading and vocabulary-learning tasks. A total of 976 English high school pupils (564 aged 11 to 13 years and 412 aged 14 to 16 years) completed reading tasks on laptop computers while exposed to different levels of classroom noise played through headphones. The tasks consisted of reading science texts, which were followed by multiple-choice questions probing comprehension and word … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 55 publications
0
49
0
Order By: Relevance
“…The systematic review identified nine studies of associations of environmental noise on cognition [39,48,[84][85][86][87][88][89][90]. Studies examined child and adult samples.…”
Section: Grade Evaluationmentioning
confidence: 99%
See 2 more Smart Citations
“…The systematic review identified nine studies of associations of environmental noise on cognition [39,48,[84][85][86][87][88][89][90]. Studies examined child and adult samples.…”
Section: Grade Evaluationmentioning
confidence: 99%
“…Two other studies known to the authors were also added [94,95], along with another recent conference paper [93]. Six studies were excluded after data extraction (Appendix A.2) which included two studies which reported experimental studies [84,85]; one that reported on mental health and not cognition and had already been identified in the search for mental health [39]; one which did not report on noise exposure per se [89], and another study which reported an ADHD outcome, which was moved to the mental health review [48]. One study reported on attitudes to noise within the school and did not report a cognitive outcome [90].…”
Section: Grade Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…For obvious technical reasons, neither the operator nor the outcome assessor was blinded in any of four randomized studies we reviewed (Connolly et al., 2019; Jones et al., 2015; Prodi & Visentin, 2015; Yang et al., 2017). A summary of the judgments of the authors of this review regarding the risk of biases at the level of individual studies for these four randomized studies is provided in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…Among all students responding, fewer than one out of three (29.6%) reported being taught how to protect their hearing during noisy events or activities. A loud sound level in a classroom is not just an annoyance; it can also disrupt academic performance and educational activities (3,4). Certain classroom environments as well as some related school activities can be loud and might contribute to NIHL (5,6).…”
mentioning
confidence: 99%